STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SELF-REGULATION SISWA MELALUI KEGIATAN KEAGAMAAN - Zulfah El Husnah; Syaikhu Rozi; Hajar Nurma Wachidah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2025)
This study examines the strategies of Islamic Religious Education (PAI) teachers in enhancing students’ religious activities at school. The phenomenon addressed is the tendency of students to perform religious practices due to external pressure rather than personal awareness. The purpose of this study is to describe students’ self-regulation abilities and the strategies employed by teachers to foster spiritual awareness through an integrated and contextual approach. This research adopts a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observation, and documentation. The findings reveal that students developed from externally regulated compliance to internally regulated worship practices. The strategies implemented by PAI teachers include spiritual assessment (AKDS), personal–empathetic approaches, integration of religious values into learning, assignment of responsibilities in religious activities, and collaboration with homeroom teachers and guidance counselors. Teachers also provide direct role modeling and continuous motivation. These findings contribute to strengthening a self-regulation-based spiritual education model.